Burden of disease, research funding and innovation in the UK: Do new health technologies reflect research inputs and need?. (April 2013) - Ward, Derek; Martino, Orsolina; Packer, Claire; Simpson, Sue; Stevens, Andrew
Objectives: New and emerging health technologies (innovation outputs) do not always reflect conditions representing the greatest disease burden. We examine the role of research and development (R&D) funding in this relationship, considering whether areas with fewer innovative outputs receive an appropriate share of funding relative to their disease burden. Methods: We report a retrospective observational study, comparing burden of disease with R&D funding and innovation output. UK disability-adjusted life years (DALYs) and deaths came from the World Health Organization (WHO) 2004 Global Burden of Disease estimates; funding estimates from the UK Clinical Research Collaboration's 2006 Health Research Analysis; and innovation output was estimated by the number of new and emerging technologies reported by the National Institute for Health Research (NIHR) Horizon Scanning Centre between 2000 and 2009. Results: Disease areas representing the biggest burden were generally associated with the most funding and innovation output; cancer, neuropsychiatric conditions and cardiovascular disease together comprised approximately two-thirds of DALYs, funding and reported technologies. Compared with DALYs, funding and technologies were disproportionately high for cancer, and technologies alone were disproportionately high for musculoskeletal conditions and endocrine/metabolic diseases. Neuropsychiatric conditions had comparatively few technologies compared to both DALYs and funding. The relationship between DALYs and innovation output appeared to be mediated by R&D funding. Conclusions: The relationship between burden of disease and new and emerging health technologies for different disease areas is partly dependent on the associated level of R&D funding (input). Discrepancies among key groups may reflect differential focus of research funding across disease areas.